“Plandemic” and “Hunger Virus”: A Morpho-pragmatic Study of Coronavirus Related Neologisms - Ogban Uwen , God’sgift; Magor Ellah, Stephen (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
This study analyses some neologisms that were created by some Nigerian users of English language as a result of the global coronavirus pandemic. The theoretical framework considered for this study is van Dijk’s Context Models and Lieb’s Process Model of Words Formation. A corpus of one hundred and ninety-five neologisms were selected from social media, electronic media, print media, and participants’ observation, particularly between February and December, 2020. The study identifies six discursive contexts: context of preventive protocols, context of identifying the condition, context of treatment, context of enforcement of restriction order, context of supportive measure, and context of corruption. The findings further reveal that the discursive contexts are indexed by acronyms, simple words, compound words, blended words, clipped words, unusual collocations, and phrasal/clausal creations. The creations were meant to describe the consequential circumstances in the health emergency in the Nigerian sociolinguistic milieu. The linguistic implications include the fact that the resources of English as Second Language (ESL) in Nigeria are rich enough to attend to the communication exigencies of the non-native speakers. The study concludes that the neologisms were devised by the interlocutors for the purposes of public enlightenment, expression of hope and collaboration, and to solicit general compliance with the preventive and treatment protocols in order to flatten the COVID-19 curve.